Komunitas iman sebagai ruang formasi moral: Reinterpretasi pendekatan “praksis bersama” Thomas Groome bagi pendidikan Kristiani multikultural Indonesia - Woenardi, Thinna Naftali (KURIOS, 2026)
Christian education in multicultural Indonesia faces distinctive challenges in moral formation amidst religious, ethnic, and cultural diversity. This article reinterprets Thomas Groome's "Shared Christian Praxis" as a theological-pedagogical framework for moral formation within faith communities in plural contexts. Using a hermeneutic-reconstructive method that combines conceptual analysis and contextual synthesis with Indonesian local wisdom, the study argues that Groome's dialogical pedagogy, when placed in critical dialogue with communitarian ecclesiology and Indonesian cultural grammar, yields a distinctive model of character formation that respects diversity without sacrificing Christian particularity. This article constructs a critical-constructive reinterpretation that identifies Groome's limitations for non-Western contexts and recalibrates his five movements through the cultural lenses of gotong royong, musyawarah-mufakat, and tepo seliro. The resulting framework positions the faith community as the primary locus of moral formation through dialogical praxis at the level of epistemic posture, communal ritual, and pedagogical flow, offering concrete markers for institutional transformation.   Abstrak Pendidikan Kristiani di Indonesia yang multikultural menghadapi tantangan khas dalam formasi moral di tengah keragaman agama, etnis, dan budaya. Artikel ini mereinterpretasi pendekatan "praksis Kristiani bersama" Thomas Groome sebagai kerangka teologis-pedagogis bagi formasi moral dalam komunitas iman dalam konteks plural. Dengan metode hermeneutis-rekonstruktif yang memadukan analisis konseptual dan sintesis kontekstual dengan kearifan lokal Indonesia, studi ini berargumen bahwa pedagogi dialogis Groome, ketika didialogkan secara kritis dengan eklesiologi komunitarian dan tata budaya Indonesia, menghasilkan model pembentukan karakter yang menghargai keragaman tanpa mengorbankan kekhasan Kristiani. Artikel ini membangun reinterpretasi kritis-konstruktif yang mengidentifikasi keterbatasan Groome bagi konteks non-Barat dan mengalibrasi ulang lima gerakannya melalui lensa gotong royong, musyawarah-mufakat, dan tepo seliro. Kerangka yang dihasilkan memosisikan komunitas iman sebagai lokus utama formasi moral melalui praksis dialogis pada level sikap epistemik, ritus komunal, dan alur pedagogis, sekaligus menawarkan penanda konkret bagi transformasi institusional.